Combination of Bacteriophages and Antibiotics for Prevention of Vascular Graft Infections-An In Vitro Study - Stefan Ruemke; Evgenii Rubalskii; Christina Salmoukas; Kristina Hermes; Ruslan Natanov; Tim Kaufeld; Oleksandr Gryshkov; Vitalii Mutsenko; Maxim Rubalsky; Karin Burgwitz; Birgit Glasmacher; Axel Haverich; et al. (MDPI AG, 2023)
(1) Background: Implant-associated bacterial infections are usually hard to treat conservatively due to the resistance and tolerance of the pathogens to conventional antimicrobial therapy. Bacterial colonization of vascular grafts may lead to life-threatening conditions such as sepsis. The objective of this study is to evaluate whether conventional antibiotics and bacteriophages can reliably prevent the bacterial colonization of vascular grafts. (2) Methods: Gram-positive and Gram-negative bacterial infections were simulated on samples of woven PET gelatin-impregnated grafts using Staphylococcus aureus and Escherichia coli strains, respectively. The ability to prevent colonization was evaluated for a mixture of broad-spectrum antibiotics, for strictly lytic species-specific bacteriophage strains, and for a combination of both. All the antimicrobial agents were conventionally tested in order to prove the sensitivity of the used bacterial strains. Furthermore, the substances were used in a liquid form or in combination with a fibrin glue. (3) Results: Despite their strictly lytic nature, the application of bacteriophages alone was not enough to protect the graft samples from both bacteria. The singular application of antibiotics, both with and without fibrin glue, showed a protective effect against S. aureus (0 CFU/cm2), but was not sufficient against E. coli without fibrin glue (M = 7.18 × 104 CFU/cm2). In contrast, the application of a combination of antibiotics and phages showed complete eradication of both bacteria after a single inoculation. The fibrin glue hydrogel provided an increased protection against repetitive exposure to S. aureus (p = 0.05). (4) Conclusions: The application of antibacterial combinations of antibiotics and bacteriophages is an effective approach to the prevention of bacteria-induced vascular graft infections in clinical settings.